The influence of dissipation on the quasielastic barrier distributions of some nuclear systems - Piasecki Eryk; Colucci Giulia; Trzcińska Agnieszka; Wolińska-Cichocka Marzena (EPJ Web of Conferences)
We present the review of last studies concerning the interpretation of barrier distributions. In some cases, dissipation strongly influences the shape of quasielastic and fusion barrier distributions, smoothing their structure caused by collective excitations. In instances of dissipation due to non-collective excitations and relatively weak transfers, the CCRMT model works reasonably well. In cases where dissipation is caused rather by transfer channels, one should take into account the strong dependence of the transfer couplings on the transfer Q-value distributions.